Studies on the survival and development of field-caught snail Lymnaea rubiginosa in the laboratory - Widjajanti, S (Indonesian Animal Sciences Society, 1998)
Lymnaea rubiginosa was collected from two habitats in order to observe their survival and growth rate including their egg production, hatching time and the time they needed to reach maturity. One of the habitat is rice fields in Bogor (subdistricts of Ciomas and Ciampea) and the other is a pond in Bogor Botanical Garden. In the laboratory those snails were kept in separate aquarium and grouped according to their shell length. The result showed that the longer the snail length the shorter their survival rate and less egg production. Moreover, the snails collected from rice fields were infected with Echinostoma sp. And Chaetogaster sp., while the snails from the pond were only infected with Chaetogaster sp. The hatching time is between 10-14 days, and to reach maturity, with shell length about 1 cm, they need about 6 weeks. Â Key words : Lymnaea rubiginosa, survival, growth rate, fasciolosis